Load of nutrients and organic substances of the Don River basin (Severskyi Donets sub-basin) - Ukhan, Olha; Osadcha, Nataliia (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2023)
Formulation of the problem. The main danger of organic substances is the use of large amounts of oxygen for its oxidation. As a result, there are conditions of oxygen deficiency in polluted water sometimes to the formation of hypoxia. It leads to significant violations of biological groups and the death of certain species. The increase of nutrients leads to the uncontrolled development of higher aquatic plants and algae. It caused to undesirable imbalance of organisms in the water body and to decrease in water quality. So, control over the content of nutrients and organic substances in water is one of the important factors to ensure the proper functioning of aquatic ecosystems and maintain water quality.The Severskiy Donets river basin is a quite difficult water object with a variety of natural conditions. Water resources of the Severskyi Donets River serve to provide drinking and industrial water supply, agricultural needs and recreation function.Aim of the research is to determine the peculiarities of loading rivers of the Severskyi Donets basin with nutrients and organic substances.Methods. For the purpose of research, the state register 2TP-Vodhosp was used. It contains information about removal of pollutants from utilities and industrial enterprises. Statistical data about the number of population and settlements, distribution by the territory of the basin were borrowed from the database of the State Statistics Service of Ukraine and the Institute of Demography and Social Research.Scientific novelty of the work is that for the first time the loading of nutrients and organic substances for all first-order tributaries in the Severskyi Donets basin was calculated.Practical value. Analys of the main anthropogenic loads in the Severskyi Donets river basin and their impacts can be used for composition of the River Basin Management Plan as an important component. It may serve as a basis for the development of measures for surface water bodies and the river basin as a whole in order to achieve defined environmental goals.Results. The main load of nutrients and organic compounds is caused by cities with a population equivalent (PE) more than 100 thousand people.The rivers of the Uda sub-basin are the most polluted by these compounds (as a part of municipal sewage) mainly due to the influence of Kharkiv city. The amount of organic matter that enters with the industrial wastewater is also the largest for the Uda sub-basin. Among the industrial enterprises within the Severskyi Donets basin, the largest number of nutrients was diverted by PJSC NKMZ in Kramatorsk city to the rivers of the Kazenny Torets sub-basin and PJSC Severodonetsk Association "Azot" directly to the Severskyi Donets River. The main role in organic pollution from the rural population is played by 5 sub-basins: Velyka Kamyanka, Kazenny Torets, Severskyi Donets, Udy, Aidar. In general, they form 59% of the total organic substances load. The largest inflow of nitrogen and phosphorus compounds is observed to the sub-basins of the rivers Luhan, Kazennyi Torets, Udy, Aidar, Oskol and the Severskyi Donets.